Access to Digital Finance: Equity Crowdfunding across Countries and Platforms - Saul Estrin; Susanna Khavul; Alexander S. Kritikos; Jonas Löher (Institute of Labor Economics (IZA), 2023)
Financing entrepreneurship spurs innovation and economic growth. Digital financial platforms that crowdfund equity for entrepreneurs have emerged globally, yet they remain poorly understood. We model equity crowdfunding in terms of the relationship between the number of investors and the amount of money raised per pitch. We examine heterogeneity in the average amount raised per pitch that is associated with differences across three countries and seven platforms. Using a novel dataset of successful fundraising on the most prominent platforms in the UK, Germany, and the USA, we find the underlying relationship between the number of investors and the amount of money raised for entrepreneurs is loglinear, with a coefficient less than one and concave to the origin. We identify significant variation in the average amount invested in each pitch across countries and platforms. Our findings have implications for market actors as well as regulators who set competitive frameworks.
Keywords: D26; G23; G41; L26; 330; equity crowdfunding; soft information; entrepreneurship; finance; financial access and inclusion